Beneficial effects of berberine in the treatment of diabetes and its complications - Liu, Shanyao; Shen, Jie; Xu, Fanghui; Niu, Lu; Wang, Fengchan; Zhao, Guojing (Frontiers in Pharmacology, 2026)
Coptis chinensis (Huanglian), a key component in numerous classical Chinese herbal formulas, is traditionally applied for treating metabolic diseases based on its activity including clear heat, dry dampness, purge fire, and detoxify. Berberine (BBR), one key active component from Coptis chinensis, was contained in numerous classical Chinese herbal formulas for improving insulin resistance and regulating blood glucose levels, making them applicable for diabetes mellitus (DM) treatment. Clinical trials confirm that BBR monotherapy reduces glycated hemoglobin (HbA1c) by 1.5% in T2DM patients comparable to metformin. This review aims to explore its applications and current research progress in DM therapy. This article systematically reviews the modern separation, extraction, and purification techniques for BBR, its molecular pharmacological mechanisms, and advances in novel delivery technologies for diabetes treatment. This review synthesizes evidence that BBR exerts its anti-diabetic effects through multi-tiered mechanisms converging on the amelioration of insulin resistance and systemic inflammation. The findings provide a theoretical foundation for optimizing BBR’s clinical application and promote the transformation of traditional Chinese medicine from empirical usage to a scientific and standardized therapeutic paradigm. By integrating BBR’s multi-target pharmacology with cutting-edge delivery technologies, this review provides a transformative perspective, positioning BBR not merely as a natural product but as a scaffold for the rational development of next-generation, multi-target diabetes therapeutics.